2023
DOI: 10.1186/s12879-023-08800-0
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the role of neutrophil to lymphocyte ratio in neonatal sepsis

Jingyang Chen,
Sanaz Yasrebinia,
Arshin Ghaedi
et al.

Abstract: Introduction The neutrophil to lymphocyte ratio (NLR), an inflammatory biomarker, measures innate-adaptive immune system balance. In this systematic review and meta-analysis, we aim to analyze the current literature to evaluate the diagnostic role of NLR in neonatal sepsis. Methods PubMed, Web of Science, and Scopus were used to conduct a systematic search for relevant publications published before May 14, 2022. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Results of this study demonstrated an overall sensitivity of 0.88 (95% CI: 0.77–0.94) and a pooled specificity of 0.78 (95% CI: 0.65–0.87) with an overall AUC value of 0.90 (0.87, 0.92). Compared to other biomarkers, the pooled sensitivity in this meta-analysis was higher than the pooled sensitivity (0.79) in Chen et al’s meta-analysis investigating neutrophil to lymphocyte ratio (NLR) in the diagnosis of sepsis, while the specificity was lower than that (0.91) in Chen et al’s meta-analysis [ 30 ]; the comparison between PSP and calprotectin (sensitivity: 0.88 vs. 0.77, specificity: 0.78 vs.0.85) was similar to NLR [ 31 ]; Poggi’s meta-analysis assessing the accuracy of presepsin for the sepsis diagnosis showed that the pooled sensitivity and specificity were 0.93 (95% CI, 0.86–0.95) and 0.91 (95% CI, 0.85–0.95), respectively, which were higher than PSP [ 32 ]; the overall sensitivity and specificity were higher than those of CRP and PCT [ 33 ].…”
Section: Discussionmentioning
confidence: 62%
“…Results of this study demonstrated an overall sensitivity of 0.88 (95% CI: 0.77–0.94) and a pooled specificity of 0.78 (95% CI: 0.65–0.87) with an overall AUC value of 0.90 (0.87, 0.92). Compared to other biomarkers, the pooled sensitivity in this meta-analysis was higher than the pooled sensitivity (0.79) in Chen et al’s meta-analysis investigating neutrophil to lymphocyte ratio (NLR) in the diagnosis of sepsis, while the specificity was lower than that (0.91) in Chen et al’s meta-analysis [ 30 ]; the comparison between PSP and calprotectin (sensitivity: 0.88 vs. 0.77, specificity: 0.78 vs.0.85) was similar to NLR [ 31 ]; Poggi’s meta-analysis assessing the accuracy of presepsin for the sepsis diagnosis showed that the pooled sensitivity and specificity were 0.93 (95% CI, 0.86–0.95) and 0.91 (95% CI, 0.85–0.95), respectively, which were higher than PSP [ 32 ]; the overall sensitivity and specificity were higher than those of CRP and PCT [ 33 ].…”
Section: Discussionmentioning
confidence: 62%
“…Elevated neutrophil and reduced lymphocyte counts have been associated with poor outcomes in emergency medicine in general ( 84 ). The NLR response in sepsis is irrespective of age as it is also observed in neonatal sepsis ( 85 , 86 ). We believe that our I°I biomarker profiles may be a reflection of this response, as some of the elevated biomarkers are cell-type specific for neutrophils e.g.…”
Section: Discussionmentioning
confidence: 67%